The Role of HDAC6 in TDP-43-Induced Neurotoxicity and UPS Impairment - Lee, Shinrye; Kwon, Younghwi; Kim, Seyeon; Jo, Myungjin; Jeon, Yu-Mi; Cheon, Mookyung; Lee, Seongsoo; Kim, Sang Ryong; Kim, Kiyoung; Kim, Hyung-Jun (Frontiers in Cell and Developmental Biology, 2020)
Transactive response DNA-binding protein 43 (TDP-43)-induced neurotoxicity is currently well recognized as a contributor to the pathology of amyotrophic lateral sclerosis (ALS), and the deposition of TDP-43 has been linked to other neurodegenerative diseases, such as frontotemporal lobar degeneration (FTLD) and Alzheimer’s disease (AD). Recent studies also suggest that TDP-43-induced neurotoxicity is associated with ubiquitin-proteasome system (UPS) impairment. Histone deacetylase 6 (HDAC6) is a well-known cytosolic deacetylase enzyme that suppresses the toxicity of UPS impairment. However, the role of HDAC6 in TDP-43-induced neurodegeneration is largely unknown. In this study, we found that HDAC6 overexpression decreased the levels of insoluble and cytosolic TDP-43 protein in TDP-43-overexpressing N2a cells. In addition, TDP-43 overexpression upregulated HDAC6 protein and mRNA levels, and knockdown of Hdac6 elevated the total protein level of TDP-43. We further found that HDAC6 modulates TDP-43-induced UPS impairment via the autophagy-lysosome pathway (ALP). We also showed that TDP-43 promoted a short lifespan in flies and that the accumulation of ubiquitin aggregates and climbing defects were significantly rescued by overexpression of HDAC6 in flies. Taken together, these findings suggest that HDAC6 overexpression can mitigate neuronal toxicity caused by TDP-43-induced UPS impairment, which may represent a novel therapeutic approach for ALS.